Shortening critical period of weed control at soybean by residual herbicide mixtures - Roncatto, Eduardo (2023)
Background: Weed interference in the early stages of soybean development can compromise its yield. The use of herbicides with residual effects at the time of sowing is an alternative to reduce weed density and emergence time, consequently, the damage caused by their interference. Therefore, weed development can be reduced, which can result in easier post-emergence control. The combination of herbicide modes of action extends the spectrum of control and delays herbicide resistance evolution. Objective: This work aimed to determine the onset of the critical period of weed control (CPWC) from the application of residual herbicides mixtures at soybean sowing. Methods: Two experiments were carried out in 2021/2022, the first in a conventional tillage system with increasing periods of soybean/ weeds coexistence (14, 28, 42, and 56 days after crop emergence). The second experiment consisted of a no-tillage system with soybean/weeds coexistence for 30, 45, 60, 75, and 90 days after crop emergence. On the day of soybean sowing, mixtures of the herbicides diclosulam + pyroxasulfone, flumioxazin + pyroxasulfone and diuron + sulfentrazone were applied, in addition to the untreated check. Soybean yield was evaluated evaluated upon harvest and data compared by non-linear regressions to CPWC determination. Results: The application of residual herbicides can allowing reduces losses relative to the untreated control by up to 57%. CPWC beginning can be extended from eight to forty days, depending on mixes and acceptable losses. Conclusions: The use of the mixture of residual herbicides are a good option for weed interference reduction for soybean crop.